The Global Incidence, Mortality, and Burden of Breast Cancer in 2019: Correlation With Smoking, Drinking, and Drug Use - Allahqoli, Leila; Mazidimoradi, Afrooz; Momenimovahed, Zohre; Rahmani, Azam; Hakimi, Sevil; Tiznobaik, Azita; Gharacheh, Maryam; Salehiniya, Hamid; Babaey, Farah; Alkatout, Ibrahim (Frontiers in Oncology, 2022)
Background Female breast cancer (FBC) is the most common type of cancer and is associated with a considerable disease burden as well as significant mortality rates. The present study aimed to provide an update on the incidence, mortality, and burden of FBC in 2019, based on the Global Burden of Disease (GBD) Study. Materials The incidence, death rate, disability-adjusted life years (DALYs), years of life lost (YLLs), years lived with disability (YLDs), the age-standardized rates (ASR) of FBC in 204 countries, and a variety of classifications, were retrieved from the Global Burden of Disease Study. Data on tobacco use, alcohol consumption, and drug use were collected. The incidence, mortality, and burden of FBC were registered and compared between regions. Associations between age-standardized incidence rates and age-standardized mortality rates of FBC with smoking, drinking, and drug use were determined. Results The highest incidence of FBC was observed in countries with a high socioeconomic status such as those of the European continent. Despite the lower incidence of FBC in countries with a low socio-demographic index (SDI), mortality rates secondary to FBC are higher in these countries than in high-income countries. The highest age-standardized mortality rate has been reported in the Eastern Mediterranean Region (EMRO), followed by the African Region (AFRO). The highest age-standardized rates of DALY and YLL per 100,000 population in 2019 were observed in lower-income countries, while the highest ASR of YLD per 100,000 population was reported in high-income countries. Conclusion The present GBD-based study provides a comprehensive review of the incidence, mortality, and burden of FBC in 2019. The incidence of FBC is higher in regions with a higher socioeconomic status, whereas mortality rates and DALYs are higher in poorly developed regions. We suggest better screening measures and early detection programs for the latter regions.